Public Policies in the Field of Advanced Materials: International Tendencies and Subsidies to the National Policy for Advanced Materials in Brazil - Bellucci, Felipe Silva; Souza Paula, Maria Carlota (TECHNO REVIEW. International Technology, Science and Society Review /Revista Internacional de Tecnología, Ciencia y Sociedad, 2021)
Currently, advanced materials are a source of the interest for private sector, since they are regarded as the foundation for the promotion of technology-based innovation and, also, because they have the potential to add value and competitive differential. Considering the efforts of the Brazilian Ministry of Science, Technology, Innovations and Communications, which has established advanced materials as a priority, this work presents an analysis of the most important international public policies in the field of advanced materials, thus identifying their main characteristics, tendencies and priorities, with intent of subsidizing the devising of a National Plan for Advanced Materials in Brazil.